Pouch Versus No Pouch Following Total Gastrectomy: Meta-analysis of Randomized and Non-randomized Studies. Issue 6 (June 2019) - Syn, Nicholas L.; Wee, Ian; Shabbir, Asim; Kim, Guowei; So, Jimmy Bok-Yan
Abstract : Objective: The aim of the study was to assess the impact of pouch reconstruction on perioperative outcomes, postprandial symptoms, nutritional and anthropometric parameters, and overall quality of life after total gastrectomy for gastric malignancy. Summary Background Data: The short-term perioperative risks and longer term functional value of creating a small-bowel reservoir after total gastrectomy are contended. Methods: A search for randomized and non-randomized studies comparing reconstruction with or without a pouch was conducted. Treatment effects were computed using pairwise random-effects meta-analysis and meta-regression, and the systematic review was conducted in accordance with PRISMA and MOOSE guidelines. Results: A total of 17 randomized trials and 8 observational studies involving 1621 participants were included. Pouch creation is associated with an increased operation time [259.3 vs 235.8 min; weighted mean difference (WMD) 23.5, 95% confidence interval (CI) 9.8–37.2], but not hospitalization duration. There was no difference in overall postsurgical complications, including anastomotic leak and abdominal abscess. Pouch formation markedly reduces the risk of dumping syndrome at 3 to 6 months [8.1% vs 32.4%; risk ratios (RR) 0.36, 95% CI, 0.21–0.60] and 12 to 24 months (2.8% vs 23.6%; RR 0.27, 95% CI, 0.16–0.46). The functional advantages of pouch reconstruction persist at 1 to 2 years, with aggregated data indicating considerably lower risks of esophagitis and heartburn (63% relative reduction), dumping syndrome (73% relative reduction), and food intake disturbance (50% relative reduction). At 12 to 24 months, albumin levels (40.5 vs 37.9 g/L; WMD 2.59, 95% CI, 1.35–3.84) and body mass index (22.2 vs 20.9 kg/m 2 ; WMD 1.28, 95% CI, 0.61–1.94) are significantly higher among participants with a pouch. Conclusions: Pouch creation improves long-term functional and nutritional outcomes after total gastrectomy, without greater perioperative morbidity. Abstract : Supplemental Digital Content is available in the text